Solvent-free processing of lignin into robust room temperature phosphorescent materials - Min Wang; Wei-Ming Yin; Yingxiang Zhai; Jingyi Zhou; Shouxin Liu; Jian Li; Shujun Li; Tony D. James; Zhijun Chen (Nature Communications)
Abstract Producing room temperature phosphorescent (RTP) materials from biomass resources using a solvent free method is essential but hard to achieve. Here, we discovered that lignin dissolved well in the liquid monomer, 2-hydroxyethyl acrylate (HEA), due to extensive hydrogen bonding and non-bonding interactions between lignin and HEA. Motivated by this discovery, we developed a solvent free system consisting of HEA and urethane dimethacrylate (UDMA) for converting lignin into RTP materials. With this design, lignin generated radicals upon UV irradiation, which initiated the polymerization of HEA (as monomer) and UDMA (as crosslinker). The as-obtained polymer network rigidifies lignin and activates the humidity/water-resistant RTP of lignin with a lifetime of 202.9 ms. Moreover, the afterglow color was successfully tuned to red after loading with RhB via energy transfer (TS-FRET). Using these properties, the as-developed material was used as photocured multiple-emission RTP inks, luminescent coatings and a smart anti-counterfeiting logo for a medicine bottle.